Effects of aerobic exercise on hippocampal formation volume in people with schizophrenia: a systematic review and meta-analysis with original data from a randomized-controlled trial - Röll, Lukas; Fischer, Tim; Keeser, Daniel; Papazov, Boris; Lembeck, Moritz; Papazova, Irina; Greska, David; Muenz, Susanne; Schneider-Axmann, Thomas; Sykorova, Eliska; Thieme, Cristina E.; Vogel, Bob O.; et al. (Psychological medicine, 2024)
BackgroundThe hippocampal formation represents a key region in the pathophysiology of schizophrenia. Aerobic exercise poses a promising add-on treatment to potentially counteract structural impairments of the hippocampal formation and associated symptomatic burden. However, current evidence regarding exercise effects on the hippocampal formation in schizophrenia is largely heterogeneous. Therefore, we conducted a systematic review and meta-analysis to assess the impact of aerobic exercise on total hippocampal formation volume. Additionally, we used data from a recent multicenter randomized-controlled trial to examine the effects of aerobic exercise on hippocampal formation subfield volumes and their respective clinical implications.MethodsThe meta-analysis comprised six studies that investigated the influence of aerobic exercise on total hippocampal formation volume compared to a control condition with a total of 186 people with schizophrenia (100 male, 86 female), while original data from 29 patients (20 male, 9 female) was considered to explore effects of six months of aerobic exercise on hippocampal formation subfield volumes.ResultsOur meta-analysis did not demonstrate a significant effect of aerobic exercise on total hippocampal formation volume in people with schizophrenia (g = 0.33 [−0.12 to 0.77]), p = 0.15), but our original data suggested significant volume increases in certain hippocampal subfields, namely the cornu ammonis and dentate gyrus.ConclusionsDriven by the necessity of better understanding the pathophysiology of schizophrenia, the present work underlines the importance to focus on hippocampal formation subfields and to characterize subgroups of patients that show neuroplastic responses to aerobic exercise accompanied by corresponding clinical improvements.